Pattern of Time-to-Surgery in Patients With Breast Cancer at Different Stages of the COVID-19 Pandemic - Chen, Ruixian; Yang, Jiqiao; Zhao, Xin; Fu, Zhoukai; Wang, Zhu; Qiu, Changjian; Wu, Yunhao; Yang, Ruoning; Liu, Weijing; Huang, Ya; Chen, Jie (Frontiers in Oncology, 2022)
Background The management of cancer surgeries is under unprecedented challenges during the COVID-19 pandemic, and the breast cancer patients may face a time-delay in the treatment. This retrospective study aimed to present the pattern of time-to-surgery (TTS) and analyze the features of breast cancer patients under the different stages of the COVID-19 pandemic. Methods Patients who received surgeries for breast cancers at West China Hospital between February 15, 2020 and April 30, 2020 (the outbreak and post-peak stages), and between March 10, 2021 and May 25, 2021 (the normalization stage) were included. TTS was calculated as the time interval between the pathological diagnosis and surgical treatment of breast cancer patients. And the pandemic was divided into three stages based on the time when the patients were pathologically diagnosed and the severity of pandemic at that time point. TTS, demographic and clinicopathological features were collected from medical records. Results A total of 367 patients were included. As for demographic features, it demonstrated statistically significant differences in insurance type (p<0.001) and regular screening (p<0.001), as well as age (p=0.013) and menstrual status (p=0.004). As for clinicopathological features, axillary involvement (p=0.019) was a factor that differed among three stages. The overall TTS was 23.56 ± 21.39 days. TTS for patients who were diagnosed during the outbreak of COVID-19 were longer than those diagnosed during pandemic post-peak and normalization stage (p<0.001). Pandemic stage (p<0.001) and excision biopsy before surgery (OR, 6.459; 95% CI, 2.225-18.755; p=0.001) were markedly correlated with the TTS of patients. Conclusions TTS of breast cancer patients significantly varied in different stages of the COVID-19 pandemic. And breast cancer patients’ daily lives and disease treatments were affected by the pandemic in many aspects, such as health insurance access, physical screening and change of therapeutic schedules. As the time-delay may cause negative influences on patients’ disease, we should minimize the occurrence of such time-delay. It is vital to come up with comprehensive measures to deal with unexpected situations in case the pandemic occurs.